1976
DOI: 10.1056/nejm197602192940801
|View full text |Cite
|
Sign up to set email alerts
|

Combination Chemotherapy as an Adjuvant Treatment in Operable Breast Cancer

Abstract: Prolonged cyclic combination chemotherapy with cyclophosphamide, methotrexate and fluorouracil was evaluated as adjuvant treatment to radical mastectomy in primary breast cancer with positive axillary lymph nodes. After 27 months of study, treatment occurred in 24 per cent of 179 control patients and in 5.3 per cent of 207 women given combination chemotherapy (P less than 10(-6)), the advantage appearing statistically significant in all subgroups of patients. Patients with four or more positive axillary nodes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
375
2
14

Year Published

1978
1978
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,212 publications
(408 citation statements)
references
References 14 publications
5
375
2
14
Order By: Relevance
“…Presently, combined chemotherapy is mostly prescribed in neoadjuvant, adjuvant and in metastatic settings of breast cancer. Although CMF regimen represented the gold standard in the 1970s (Bonadonna et al, 1976), anthracycline-based regimens are the mainstay of adjuvant chemotherapy for early breast cancer since the 1990s (EBCTCG, 2005) Research Group 001 demonstrated superior disease-free survival and overall survival when docetaxel was given concurrently with doxorubicin and cyclophosphamide (TAC) compared with 5-fluorouracil, doxorubicin, and cyclophosphamide (FAC) in breast cancer patients in advanced stages (Martin, 2005).However, it is still urgent to develop new regimens for patients who failed treatments containing taxanes or anthracyclines.…”
Section: Introductionmentioning
confidence: 99%
“…Presently, combined chemotherapy is mostly prescribed in neoadjuvant, adjuvant and in metastatic settings of breast cancer. Although CMF regimen represented the gold standard in the 1970s (Bonadonna et al, 1976), anthracycline-based regimens are the mainstay of adjuvant chemotherapy for early breast cancer since the 1990s (EBCTCG, 2005) Research Group 001 demonstrated superior disease-free survival and overall survival when docetaxel was given concurrently with doxorubicin and cyclophosphamide (TAC) compared with 5-fluorouracil, doxorubicin, and cyclophosphamide (FAC) in breast cancer patients in advanced stages (Martin, 2005).However, it is still urgent to develop new regimens for patients who failed treatments containing taxanes or anthracyclines.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, it would mean inducing quantitative reductions in the activities of PFK and 6PGDH and/or an increase in the activity of a-GPDH. As most drugs currently used in adjuvant therapies produce minor beneficial effects in terms of prolonged disease-free interval (Fisher et al, 1975;Bonadonna et al, 1976;Meakin et al, 1979;Baum et al, 1983;Goldhirsch et al, 1984;Howell et al, 1984), it was felt that our hypothesis might be more acceptable if it could be shown that at least some of these drugs act on carcinomas in such a way as to induce changes in activities of these enzymes. Therefore we have attempted to investigate the effects of two drugs, viz.…”
Section: Discussionmentioning
confidence: 96%
“…Role of chemotherapy in adjuvant setting was heralded when two landmark studies of adjuvant chemotherapy in breast cancer were published: one which tested L Phenyl Alanine Mustard and was reported by Fisher and colleagues in 1975, 9 and one which tested a drug combination Cyclophosphamide, Methotrexate and 5 Fluorouracil reported by Bonadonna et al 10 The revolution in cancer research can be summed up in a single sentence: cancer is, in essence, a genetic disease e Bert Vogelstein A major fillip in cancer management came in 2006 with discovery of Imatinib by Druker et al 4,11 in care of chronic myeloid leukemia wherein proof that treatment targeting specific molecular abnormalities that are unique to certain cancers could convert them into manageable chronic illnesses. Targeted therapy had come of age.…”
Section: Its Palliation Is a Daily Task Its Cure A Fervent Hope E Wmentioning
confidence: 99%